Awakening Early Conscience: Islamic Values and Religious Moderation in Syeikh Abdurrahman Shiddiq’s Syair - Sakila, Siti Risda; Putro, Khamim Zarkasih; Hibana, Hibana (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This article explores